CONCENTRATION OF HEAVY METALS IN SOIL CONTAMINATED WITH CRUDE OIL AT TWO IRAQUIAN SITES ACCORDING TO ENVIRONMENTAL INDICES OF POLLUTION (Nativa, 2023)
Contaminated soil samples were collected from the Al-Kasak refinery and Al-Qayyarah refinery in western and southern Nineveh, at specific distances in six dimensions (0, 50, 100, 150, 200, 300) meters from the source of pollution, to study the concentrations of heavy metals Pb, Mn, Ni, Cd and the effect of oil refinery pollutants on some soil pollution standards, in addition to some physical and chemical properties of the soil and their concentrations. The results showed an increase in the concentration of heavy metals in the soil near the sources of pollution, with cadmium significantly superior to the Al-Qayyarah site over Al-Kasak site (491.744 mg kg-1) and lead, nickel and manganese recorded a higher concentration at Al-Kasak site compared to Al-Qayyarah site (166.356, 114.687, 36.487 mg kg-1), respectively. The order of mineral elements in the two study sites was Cd>Pb>Ni>Mn. As for the Contamination Factor (CF), it was Cd > Pb > Ni > Mn with values of 684.50, 9.91, 5.13, and 0.1701, where the concentration factor was highly polluted for cadmium and lead, and with significant contamination for nickel, while manganese was low in contamination, cadmium recorded severe pollution at Al-Qayyarah site compared to Al-Kasak site. In contrast, lead, nickel, and manganese were significantly contaminated at the Al-Kasak site compared to Al-Qayyarah. In addition, the pollution load index (PLI) was at the level of 5.81, 4.67, highly polluted at D1 and D2, while the rest of the percentages were at the level of 2, moderate pollution, Al-Kasak site had the highest pollution (PLI) value of (6.28). At the same time, the ecological risk (ER) averaged (20534.88, 16896.71, 19867.11, 19063.14, 18721.07, 18888.61), which indicates that all the sites had very high pollution. The ecological risk index was also within the limits of very high pollution, with the highest value on D1 recorded (20568.45). The potential ecological risk of cadmium was very high at the Al-Qayyarah site, with a value of (19410.95) compared to the Al-Kasak site, where the ecological risk of lead, nickel, and manganese was very high. The ecological risk indices for the Al-Qayyarah site were higher than the Al-Kasak site. The study aims to estimate the concentration of heavy metals according to environmental indices and the impact of oil refineries on the ecosystem in raising the level of heavy metal concentration.Keywords: soil pollution; contamination factor; pollution load index; ecological risk. Concentração de metais pesados em solo contaminado com petróleo bruto em duas localidades iraquianas de acordo com índices ambientais de poluição RESUMO: Amostras de solo contaminado foram coletadas da refinaria Al-Kasak e da refinaria Al-Qayyarah no oeste e sul de Nínive, nas distâncias específicas de 0, 50, 100, 150, 200 e 300 metros da fonte de poluição. Estudou-se as concentrações dos metais pesados Pb, Mn, Ni, Cd e os seus efeitos em alguns padrões de poluição do solo e em propriedades físicas e químicas do solo. Os resultados mostraram um aumento na concentração de metais pesados no solo próximo às fontes de poluição, com cádmio significativamente superior em Al-Qayyarah quando comparado com Al-Kasak (491.744 mg kg-1); chumbo, níquel e manganês apresentaram concentrações mais elevadas em Al-Kasak (166,356, 114,687, 36,487 mg kg-1, respectivamente). A ordem dos elementos minerais nos dois locais de estudo foi Cd>Pb>Ni>Mn. Quanto ao Fator de Contaminação (FC), a ordem observada foi Cd > Pb > Ni > Mn com valores de 684,50, 9,91, 5,13 e 0,1701; o fator de concentração indica alta poluição para cádmio e chumbo, e com contaminação significativa para níquel; manganês apresentou baixos fatores de contaminação, e, cádmio gerou o grau de poluição severa em Al-Qayyarah quando comparado com Al-Kasak. Em contraste, chumbo, níquel e manganês foram significativamente contaminados no local de Al-Kasak em comparação com Al-Qayyarah. Além disso, o índice de carga poluente (PLI) ficou no nível 5,81, 4,67, altamente poluído em D1 e D2, enquanto o restante dos percentuais ficou no nível 2, poluição moderada, o local de Al-Kasak teve a maior poluição (PLI) valor de (6,28). Ao mesmo tempo, o risco ecológico (ER) foi médio (20.534,88, 16.896,71, 19.867,11, 19.063,14, 18.721,07, 18.888,61), o que indica que todos os locais apresentavam poluição muito elevada. O índice de risco ecológico também esteve dentro dos limites de poluição muito elevada, tendo sido registado o valor mais elevado no D1 (20568,45). O risco ecológico potencial do cádmio era muito elevado no local de Al-Qayyarah, com um valor de (19410,95) em comparação com o local de Al-Kasak, onde o risco ecológico de chumbo, níquel e manganês era muito elevado. Os índices de risco ecológico para o sítio Al-Qayyarah foram mais elevados do que para o sítio Al-Kasak. O estudo tem como objetivo estimar a concentração de metais pesados de acordo com índices ambientais e o impacto das refinarias de petróleo no ecossistema na elevação do nível de concentração de metais pesados.Palavras-chave: poluição do solo; fator de contaminação; índice de carga poluente; risco ecológico.